A gentle introduction to the differential equation method and dynamic concentration - Bennett, Patrick; Dudek, Andrzej (Discrete mathematics, 2022)
We discuss the differential equation method for establishing dynamic concentration of discrete random processes. We present several relatively simple examples of it and aim to make the method understandable to the unfamiliar reader who has some basic knowledge on probabilistic methods, random graphs and differential equations.